(untitled) (Andamios, Revista de Investigación Social, 2025)
Various local memory exercises reveal interesting findings on symbolic appropriation and collective learning. This article presents neighborhood memory as a community pedagogy, a self-teaching process that originates in the daily oral narratives of the territory. Regarding the methodology, four documented experiences of neighborhood memories from slums and towns in Santiago, Chile, were analyzed. The results reveal various categories of memory, highlighting the milestones, characters, places and mythologies that make up community identity. It is concluded that the exercise of territorial memory implies collective learning that articulates sociocultural narratives, creating a favorable environment for critical reflection and the transformation of the territory.